Efeitos da imidazonaftiridina na infecção pelo vírus chikungunya: atividade antiviral por uma via independente do interferon tipo 1? - Ruiz, Uriel Enrique Aquino (2022)
The Chikungunya virus (CHIKV), the causative agent of Chikungunya fever, is transmitted mainly by the bite of hematophagous mosquitoes of the Aedes genus. The disease is characterized by symptoms such as disabling arthralgias and polyarthralgia, which can persistent for months or years. Up to date, there are no antiviral drugs available to treat CHIKV manifestations. In this context, Imidazolnaphtyridine (RO8191) is a compound with antiviral activity previously reported against the Hepacivirus C (HCV) and Zika virus (ZIKV), however, the anti-CHIKV activity of RO8191 has not yet been elucidated. Therefore, this work aimed to evaluate the effects of RO8191 on CHIKV infection in vitro, employing CHIKV-nanoluc, a viral construct inserted of a reporter gene (-nanoluc), to infect baby hamster kidney cells (BHK-21). Cell viability analysis was evaluated through MTT assays and infectivity rates through luminescence assays. We developed time of drug-addition assays in different stages of the CHIKV replicative cycle, as well as BHK-CHIKV-NCT cells, that express CHIKV non-structural proteins and Renilla luciferase and EGFP reporters, were also used to analyze the effects of RO8191 on viral replication. RO8191 strongly inhibits the CHIKV replication with a selectivity index (SI) of 12.3 and 18.7 in BHK-21 and BHK-CHIKV-NCT cells, respectively. Additionally, the compound inhibited all viral stages evaluated, with higher rates of inhibition in viricidal (75.4%) and post-treatment (87%). Due to the IFN-α agonism by RO8191, and to analyze an independent of this pathway effect, assays were also developed all employing VERO-E6 cells, which do not encode type I interferons (IFN-I-/-). As a result, RO8191 presented SI of 37.3 and had effects in all viral replication steps, but mainly in viricidal (70.5%) and post-treatment (91.6%) assays. Infrared spectroscopy assays (ATR-FTIR) and molecular docking experiments were carried out and demonstrated interactions mainly between RO8191 and CHIKV glycoproteins. Our data highlights the anti-CHIKV potential exerted by RO8191, that could be future capitalized as an alternative treatment against Chikungunya fever.